1997
DOI: 10.1073/pnas.94.26.14965
|View full text |Cite
|
Sign up to set email alerts
|

Brain wave recognition of words

Abstract: Electrical and magnetic brain waves of seven subjects under three experimental conditions were recorded for the purpose of recognizing which one of seven words was processed. The analysis consisted of averaging over trials to create prototypes and test samples, to both of which Fourier transforms were applied, followed by filtering and an inverse transformation to the time domain. The filters used were optimal predictive filters, selected for each subject and condition. Recognition rates, based on a least-squa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(99 citation statements)
references
References 16 publications
(14 reference statements)
6
92
1
Order By: Relevance
“…By using all of the data again to create eight unfiltered but averaged test samples and by applying a least-squares criterion of fit, we correctly classified six of the eight syllables. This is a reasonably good result but not as good as the use of an optimal filter, as in earlier articles (1)(2)(3)(4). By using data from sensor C3 and the time interval from 107 ms after onset of stimuli to 640 ms, the optimal filtered result was classification of all eight unfiltered test samples correctly.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…By using all of the data again to create eight unfiltered but averaged test samples and by applying a least-squares criterion of fit, we correctly classified six of the eight syllables. This is a reasonably good result but not as good as the use of an optimal filter, as in earlier articles (1)(2)(3)(4). By using data from sensor C3 and the time interval from 107 ms after onset of stimuli to 640 ms, the optimal filtered result was classification of all eight unfiltered test samples correctly.…”
Section: Resultsmentioning
confidence: 62%
“…Subjects were numbered consecutively and sometimes were used in more than one of the earlier studies (1)(2)(3)(4). The same numbering is used in this article.…”
mentioning
confidence: 99%
“…One example is a study by Bhattacharya et al (2001), who found different patterns of dependencies between EEG channels while listening to different pieces of music, which are higher for listeners with musical training than for nonmusicians. Early studies on classifying auditorily presented language (words or sentences) produced good results (Suppes et al, 1997(Suppes et al, , 1998, indicating feasibility of classification using EEG signals, but to our knowledge no such effort has been made for musical material.…”
Section: Introductionmentioning
confidence: 98%
“…In (Suppes et al, 1997), it has been shown that isolated words can be recognized based on EEG and MEG recordings. In one of their experimental conditions called internal speech, the subjects were shown one out of 12 words on a screen and asked to utter this word 'silently' without using any articulatory muscles.…”
Section: Related Workmentioning
confidence: 99%
“…However, it has been shown in (Suppes et al, 1997) that subject-independent predictions are possible. It has to be taken into account, though, that their subject-independent model was built by averaging over half of their database which was much larger than ours.…”
Section: Cross Session Experimentsmentioning
confidence: 99%